Integrasi Metode E-Servqual dan Metode Fuzzy pada Pengukuran Kualitas Pelayananan aplikasi Jamsostek Mobile - Yanti, Fitri; Nugraha, Winata (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The business world continues to improvise and innovate in order to retain customers as the market becomes increasingly dynamic due to advances in information technology and telecommunications. Effective and efficient shopping, purchasing and distribution using a site design called E-Service Quality. This study seeks to ascertain what quality standards need to be improved and assess the level of service provided by Jamsostek Mobile (JMO) by utilizing E-Servqual (Service Quality) and a fuzzy approach, 20 criteria and 6 dimensions, namely efficiency, compliance, system availability, privacy, responsiveness, contacts for analysis. The findings of this study reveal that Jamsostek Mobile (JMO) customer service is of good quality. Jamsostek Mobile (JMO) performance often meets consumer expectations. Only one dimension, namely System Availability, has a negative value. 18 criteria have positive gap values ??while the other 2 have negative gap values ??based on the expected and expected defuzzification values ??of the 20 criteria. Jamsostek Mobile (JMO) users consider several characteristics to be so significant that they are assessed as top priorities using a Cartesian diagram. Even so, the Jamsostek Mobile (JMO) service is still below standard in terms of System Availability, with the requirements being that the Jamsostek Mobile (JMO) application system must function perfectly and offer excellent customer support for information requests and complaints